Offshore and coastal modelling. - Dyke, P.P.G.; Moscardini, A.O.; Robson, E.H. (New York, New York Springer-Verlag, 1985)
Lecture Notes on Coastal and Estuarine Studies; 12
Keywords: Tidal currents; Storm surges; Offshore structures; Ocean engineering